Burnout in The Digital Age: The Role of Tech Fatigue and Job Demands in Employee Well-Being - Puspita, Irma Yudit Ayu; Setiawati, Noor Lusty putri; Sulistyani, Nuraida Wahyu (PT. Anagata Sembagi Education, 2025)
This study investigates the impact of technological fatigue (tech fatigue) and job demands on employee burnout in the digital era. The rapid adoption of digital technologies has transformed work practices, but it has also created new challenges for employee well-being. Using a quantitative explanatory design, data were collected from 120 employees in technology-based and service industries through an online survey. The instruments consisted of validated scales measuring tech fatigue, job demands, and burnout, with responses assessed using a five-point Likert scale. Descriptive statistics and multiple regression analysis were applied to test the hypotheses. The findings reveal that both tech fatigue (β = 0.41, p < 0.01) and job demands (β = 0.37, p < 0.01) significantly and positively affect burnout. Together, these variables explain 52% of the variance in employee burnout. The results highlight that burnout in the digital age is not solely driven by traditional workload factors, but also by excessive exposure to digital technology. This study contributes to the Job Demands-Resources (JD-R) framework by emphasizing tech fatigue as a contemporary factor influencing burnout. Practically, the findings suggest that organizations should implement preventive strategies such as workload management, digital well-being programs, and organizational support systems to reduce burnout risk. Future research may adopt longitudinal designs, include moderating variables such as organizational support, and explore cross-industry comparisons to deepen understanding of digital-age burnout.